2018
DOI: 10.4172/2155-9600.1000734
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances In Nutritional Sciences: An Overview Of Glycans And MiRNAs

Abstract: There are many nutritional substances that humans consume on a daily basis: water, carbohydrates lipids and proteins are main biochemical components of food. But others in a smaller amount are vitamins minerals and enzymes. At a possibly lesser quantity are glycans and miRNAs. The presence of oligoglycans in all food sources has been an established fact for many years. These special carbohydrates are present as glycoconjugates (glycoproteins or glycolipids) in and on the surface of all the cells (glycocalyx) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 386 publications
(490 reference statements)
0
12
0
Order By: Relevance
“…Nevertheless, it is reported that there's a lack of evidence supporting the BTD hypothesis [18]. To date, only one serious mechanistic explanation, apart from the lectin hypothesis, has been put forward for BTD and involves the intervention of glycans [11]. Their presence in food and their particular biochemistry make them exceptionally prone to interact with human biomolecules and elicit and modulate immune and/or inflammatory responses [11,[19][20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, it is reported that there's a lack of evidence supporting the BTD hypothesis [18]. To date, only one serious mechanistic explanation, apart from the lectin hypothesis, has been put forward for BTD and involves the intervention of glycans [11]. Their presence in food and their particular biochemistry make them exceptionally prone to interact with human biomolecules and elicit and modulate immune and/or inflammatory responses [11,[19][20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, only one serious mechanistic explanation, apart from the lectin hypothesis, has been put forward for BTD and involves the intervention of glycans [11]. Their presence in food and their particular biochemistry make them exceptionally prone to interact with human biomolecules and elicit and modulate immune and/or inflammatory responses [11,[19][20][21][22]. Ultimately, these processes of inflammation and immune tolerance could be regarded as possible underlying initiators of aging and age-related diseases [23,24].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations